SISTEM OTOMATIS PENGINGAT JADWAL MENGAJAR DOSEN BERBASIS SMS (SHORT MESSAGE SERVICE) DI STMIK PPKIA PRADNYA PARAMITA MALANG (STIMATA) - ., Sujito; Sundari, Retno (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
In the normal course, a teacher can not teach that sometimes does not give the info first. Either directly to the field of teaching, students are appointed as class representative, or attach the previous announcement. Regardless of the reason for the absence of a lecturer during teaching hours, either because of forgetting or any unforeseen events, it is necessary that certain information about the status of lecturers coming, both to the campus or to students in real time. If we notice, communication devices that are the most portable and almost everyone has a cell phone or who is often called by mobile phone. This communication tool we can use to communicate verbally (call) with others, send short messages (SMS), multimedia messaging (MMS), internet access (GPRS), and even capable of streaming video directly (3G). Of some features of the mobile phone, the most frequently used feature is the SMS facility. This may be due to the ease of use and more importantly because of its economic value. Well go from here, in this study will be discussed about the use of SMS technology for the development of a system that can complement the Academic Information System that has been around Keywords: Schedule, Lecturer, SMS